Improving quantification of rainfall runoff pollutant loads with consideration of path curb and field ridge - Zengwei Yuan (Elsevier, 2021)
Quantifying the pollutant loads in rainfall runoff plays a critical role in non-point source pollution control at the watershed level. However, the retention effect of path curb in urban areas and field ridge in farmlands on surface rainfall runoff volume and pollutant loads is still unknown and paid little attention. To make it clear, we measured the height of path curb and field ridge and their effects on rainfall runoff, as well as pollutant loads in a comprehensive demonstration area in Taihu Lake basin. A localized Soil Conservation Service-Curve Number (SCS-CN) hydrological model was applied to calculate the rainfall runoff and provided support for the subsequent pollutant loads calculation, including total phosphorus, total nitrogen, ammonia nitrogen and chemical oxygen demand. The results show that the height of path curb in the study area is distributed between 0 to 1 cm and 2 to 3 cm, and the height of field ridge is clustered between 20 to 25 cm. The path curb and the field ridge reduce the runoff volume generation by 17.5% and 91.1% respectively. The path curb and the field ridge reduced more total phosphorus load than the loads of total nitrogen, chemical oxygen demand and ammonia nitrogen. The result improves our understanding on the retention effect of path curb and the field ridge on pollutant loads in rainfall runoff and provides a new idea for non-point source pollution control.